Willingness to accept a second COVID-19 vaccination booster dose among healthcare workers in Italy - Della Polla, Giorgia; Miraglia del Giudice, Grazia; Folcarelli, Lucio; Napoli, Annalisa; Angelillo, Italo Francesco, The Collaborative Working Group; Longanella, Walter; Massimo Mensorio, Mario; Cantore, Federica (Frontiers in Public Health, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is evolving with the newly emerged Omicron variant that is the dominant strain worldwide and raised concerns about the vaccine efficacy. The purposes of this survey were to examine the extent to which healthcare workers (HCWs) intends to receive the second booster dose of the COVID-19 vaccine and the factors that influence their willingness for accepting it. Methods: The study was conducted among HCWs randomly selected in four randomly selected public hospitals in the Campania region, Southern Italy. Results: A total of 496 HCWs answered the questionnaire for a response rate of 61.2%. A total of 20.8% respondents indicated a score of 10, using a 10-point Likert-type scale, regarding the usefulness of the second booster dose of the COVID-19 vaccine. Physicians, HCWs who believed that COVID-19 was a severe disease, and those who have acquired information about the second booster dose from scientific journals were more likely to have this positive attitude. Slightly more than half self-reported the willingness to receive the second booster dose. Respondents who believe that HCWs are at higher risk of being infected by SARS-CoV-2, those who have a higher believe that COVID-19 is a severe disease, and those who have a higher believe that the second booster dose is useful were more willing to receive the second booster dose. The main reasons for those who had a positive intention were to provide protection for family members and patients, whereas, the main reasons for not getting vaccinated or for uncertainty were that the dose does not offer protection against the emerging variants and the fear of its side effects. HCWs of younger age, physicians, those who have a higher believe that the second booster dose is useful, and those who were willing to receive the second booster dose were more likely to recommend the booster dose to their patients. Conclusion: Findings underscore the necessity for designing and implementing education interventions for improving second booster dose uptake and beliefs among HCWs and their capacity to recommend the vaccine to the patients.